2006
DOI: 10.1089/ars.2006.8.375
|View full text |Cite
|
Sign up to set email alerts
|

Early Involvement of ROS Overproduction in Apoptosis Induced by 7-Ketocholesterol

Abstract: Cholesterol oxidation products are increasingly considered as much more bioactive than the parent compound in the multifactor and multistep process that characterizes atherosclerosis. In particular, 7-ketocholesterol has been reported to induce oxidative stress as well as a marked pro-apoptotic effect in vascular cells including macrophages. With the aim to investigate a possible pathogenic correlation between the two events, cultivated murine macrophages were challenged with a concentration of 7-ketocholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…Among the bioactive lipids in oxLDL, oxysterols have been shown to be involved at all stages of atherosclerosis development, and they play an important role in plaque formation ( 24,25 ). In the early stage of atherosclerosis, oxysterols are involved in impairment of several endothelial functions, such as endothelial nitric-oxide synthase (eNOS) activation ( 26 ), reactive oxygen species (ROS) production ( 27 ), and regulation of the permeability barrier ( 28,29 ). In the late stage of atherosclerosis, an increase in the levels of oxysterols was shown to contribute to apoptosis of vascular cells ( 29,30 ) and degradation of extracellular matrix ( 31,32 ), which led to instability of the plaque.…”
Section: Afm Microindentationmentioning
confidence: 99%
“…Among the bioactive lipids in oxLDL, oxysterols have been shown to be involved at all stages of atherosclerosis development, and they play an important role in plaque formation ( 24,25 ). In the early stage of atherosclerosis, oxysterols are involved in impairment of several endothelial functions, such as endothelial nitric-oxide synthase (eNOS) activation ( 26 ), reactive oxygen species (ROS) production ( 27 ), and regulation of the permeability barrier ( 28,29 ). In the late stage of atherosclerosis, an increase in the levels of oxysterols was shown to contribute to apoptosis of vascular cells ( 29,30 ) and degradation of extracellular matrix ( 31,32 ), which led to instability of the plaque.…”
Section: Afm Microindentationmentioning
confidence: 99%
“…412 Besides cholesterol, its active metabolite, 7-ketocholesterol, induced ROS-mediated apoptosis of murine macrophage, and this was inhibited by metabolic inhibitors of NADPH-oxidase and the antioxidant epicatechin. 413 The alanine allele in the signal peptide of MnSOD increases its mitochondrial activity and protects macrophages against the Ox-LDL-induced apoptosis, thereby reducing the risk of coronary artery disease (CAD). 414 Cell surface expression analysis by flow cytometry and confocal microscopy revealed that Ox-LDL increased ceramide and lactosylceramide expression compared to enzymatically degraded low-density lipoprotein (E-LDL) loading and induced ceramide rafts, whereas loading with E-LDL induced cholesterol-rich micro domains.…”
Section: M a C R O P H A G E A P O P T O S I S A N D P H A G O C Y mentioning
confidence: 99%
“…In this context, several studies have shown that, in cells of the macrophage lineage, oxysterols can initiate specific signal transduction pathways, which are relevant to the development of atherosclerosis [176][177][178][179]. A recent study has demonstrated that an oxysterol mixture, of composition similar to that found in advanced human carotid plaques [173], can significantly contribute to destabilizing the fibrotic plaque, by increasing expression and activity of MMP-9, without interfering with expression and synthesis of TIMP-1 or TIMP-2.…”
Section: Introductionmentioning
confidence: 99%